Building capacity to provide innovative interventions for early psychosis in mental health professionals. (8th September 2020) - Poli, S.; Ruggeri, M.; Bonetto, C.; De Santi, K.; Miglietta, E.; Petterlini, S.; Alpi, A.; Bislenghi, L.; Bolis, T.; Fascendini, S.; Patelli, G.; Cristofalo, D.; et al.
Abstract: Despite international guidelines, cognitive behavioural therapy for early psychosis (CBTep) is still under-used in daily clinical practice, mainly due to the lack of specific skills among mental health professionals. The aim of the study was to evaluate the feasibility and efficacy of a CBTep training course and to investigate the impact of trainees' variables on the level of skills acquisition. An intensive and graded CBTep training programme consisting of 112 hours of plenary lectures, 30 hours of group supervision and 3 months of practical training was offered to mental health professionals of 65 Italian community Mental Health Centers (CMHCs). CBT expert psychologists were used as the comparison group. Participants underwent pre-planned exams to test the level of skills acquisition and were requested to complete a satisfaction survey. The vast majority of participants (93%) completed the training with medium–high evaluation scores and reported to be highly satisfied with the course. CMHCs staff members achieved high scores in the examinations and no major differences between them and CBT expert psychologists were found in most of the final exam scores. Our results support the feasibility and the efficacy of the training to build specific CBTep capacity in a large cohort of professionals working in Italian Generalist Mental Health Services. Key learning aims: (1) To understand the capacity building of a short training programme in CBT for early psychosis dedicated to community mental health professionals. (2) To consider the optimal characteristics of a CBT training programme for early psychosis. (3) To reflect on the feasibility of a CBT training programme for early psychosis in the context of Italian Community Mental Health Services.